Inter-rater Reliability and Construct Validity of the Lerner Defense Scale in Clinical and Non-clinical Groups - Rosso, Anna Maria; Airaldi, Cinzia; Camoirano, Andrea (Frontiers in Psychology, 2021)
The current study investigated the inter-rater reliability and the construct validity of the Rorschach Lerner Defense Scale (LDS). In particular, it aimed to explore the inter-rater reliability, analyzing the most frequent coding mistakes in an attempt to improve the coding guidelines, and to investigate the ability of the scale to distinguish between individuals with neurotic-level and borderline-level personality organization, according to the Psychodynamic Diagnostic Manual-2 (PDM-2), and non-clinical subjects. Eighty clinical subjects and 80 non-clinical ones participated in the study. Among the clinical subjects, 40 have borderline-level personality organization and 40 have neurotic-level personality organization. Non-clinical subjects were drawn from an archival dataset of non-clinical individuals who previously participated in a Rorschach normative study. The LDS showed substantial inter-rater reliability; however, guidelines could be improved, specifically with regard to the threshold for coding Devaluation and Idealization at level 1. Furthermore, more examples should be included in the manual about the coding of Projective Identification and Denial. The LDS distinguished borderline-level subjects from both the non-clinical and neurotic groups with regard to Devaluation and Projective Identification, with borderline-level personality organization subjects reporting higher scores than either of the two other groups. Only the Denial scale discriminated between the non-clinical and neurotic group, with the latter reporting higher scores of high-level Denial.